Emulsion Stability Tes and Effect of HNO3 Concentration in the Internal Phase on Cadmium Ion Extraction using Liquid Membrane Emulsion Technique - Sahida Sahida; Baharuddin Hamzah; Siti Nuryanti (Jurnal Akademika Kimia, 2020)
Study on the emulsion stability and cadmium ion extraction tests was performed using the liquid membrane emulsion technique. This study aimed to determine the emulsion stability between the membrane phase and the internal phase with the variation of the ratio (2:1, 1:1, 2:3, and 1:2), and to determine the maximum conditions of cadmium ion extraction in a solution including the various concentration of HNO3 solution 1, 1.5, 2, and 2.5 M. This study is a laboratory experimental method using benzoyl acetone compound as cation carrier, kerosene as membrane phase, HNO3 solution as the internal phase, span-20 and span-80 as surfactants, and cadmium solution as the sample solution. Cadmium ion concentration in the external phase was determined by UV-VIS spectrophotometer. The result showed that the emulsion stability test which produced the most stable emulsion was in the ratio of the membrane phase and the internal phase 1:1. In addition, the concentration of the HN03 solution resulted in a maximum extraction percentage of 1.5 M with an extraction percentage was 95.28%.